Integrated Tools for American Cutaneous Leishmaniasis Surveillance and Control: Intervention in an Endemic Area in Rio de Janeiro, RJ, Brazil - Cheryl Gouveia; Rosely Magalhães de Oliveira; Adriana Zwetsch; Daniel Motta-Silva; Bruno Moreira Carvalho; Antônio Ferreira de Santana; Elizabeth Ferreira Rangel (Interdisciplinary Perspectives on Infectious Diseases)
American cutaneous leishmaniasis (ACL) is a focal disease whose surveillance and control require complex actions. The present study aimed to apply integrated tools related to entomological surveillance, environmental management, and health education practices in an ACL-endemic area in Rio de Janeiro city, RJ, Brazil. The distribution of the disease, the particular characteristics of the localities, and entomological data were used as additional information about ACL determinants. Environmental management actions were evaluated after health education practices. The frequency of ACL vectors Lutzomyia (N.) intermedia and L. migonei inside and outside houses varied according to environment characteristics, probably influenced by the way of life of the popular groups. In this kind of situation environmental management and community mobilization become essential, as they help both specialists and residents create strategies that can interfere in the dynamics of vector’s population and the contact between man and vectors.